THE INFLUENCE OF SERVICE QUALITY AND PRICE PERCEPTION ON REUSE INTEREST IN GRAB MOTOR CONSUMERS IN JOMBANG - SA'ADAH , LAILATUS; MU'AROFAH , MEILIYA (IJOSMAS, 2021)
The purpose on the study he purpose of this study was to determine and analyze the effect of service quality and price perception on the re-use interest of Grab Motor consumers in Jombang. By using accidental sampling technique a number of 97 respondents. The results in this study on multiple linear regression analysis can be seen that the R square value is 0.481, which means that advertising and brand image can explain the consumer buying interest factor of 48.1% and the remaining 51.9% is explained by other factors. And in the f test, it can be seen that the probability value is 0.000 < 0.05. Thus, it can be seen that the variables of service quality and price perception simultaneously (simultaneously) have a significant effect on repurchase interest. The results of the T test show that the significance value of t = 0.000 is smaller than the value of = 0.05, which means that service quality has a significant influence on (reuse interest. The t-count value of price perception shows the significance value of t = 0.013 which is smaller than the value of = 0 .05. This means that price perception has a significant effect on interest in reuse. The better the quality of service, the higher the interest in reuse and Price is very important in determining the interest in reuse of a product/service. The better the perception of price, the higher the interest in reuse.